MEDIA E-LEARNING INTERAKTIF BERBASIS CISCO PACKET TRACER DALAM PEMBELAJARAN JARINGAN KOMPUTER DI SMK TKJ - Bunga, Nindi Bunga Iqnas; Nabila Ulfa; Jufri; Agung Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Computer network learning in vocational high schools (SMK), particularly in the Computer and Network Engineering (TKJ) department, still faces various challenges, such as students’ difficulties in understanding abstract technical concepts and limited practical facilities. This condition highlights the need for innovative, interactive, and applicable learning media. This study aims to examine the use of Cisco Packet Tracer as an interactive e-learning tool to enhance the effectiveness of computer network learning in SMK. The methodology employed is descriptive qualitative, using literature review and independent exploration of the features and implementation of Cisco Packet Tracer. The findings indicate that Cisco Packet Tracer provides a virtual learning environment that simulates real-world conditions, facilitates student understanding through hands-on simulation, and supports project-based learning. Therefore, Cisco Packet Tracer is an effective, efficient, and suitable alternative learning medium for vocational education settings.